Transplant Tolerance to Pancreatic Islets Is Initiated in the Graft and Sustained in the Spleen. Issue 8 (8th July 2013) - Gagliani, N.; Jofra, T.; Valle, A.; Stabilini, A.; Morsiani, C.; Gregori, S.; Deng, S.; Rothstein, D. M.; Atkinson, M.; Kamanaka, M.; Flavell, R. A.; Roncarolo, M. G.; et al.
Abstract: The immune system is comprised of several CD4 + T regulatory (Treg) cell types, of which two, the Foxp3 + Treg and T regulatory type 1 (Tr1) cells, have frequently been associated with transplant tolerance. However, whether and how these two Treg‐cell types synergize to promote allograft tolerance remains unknown. We previously developed a mouse model of allogeneic transplantation in which a specific immunomodulatory treatment leads to transplant tolerance through both Foxp3 + Treg and Tr1 cells. Here, we show that Foxp3 + Treg cells exert their regulatory function within the allograft and initiate engraftment locally and in a non‐antigen (Ag) specific manner. Whereas CD4 + CD25 − T cells, which contain Tr1 cells, act from the spleen and are key to the maintenance of long‐term tolerance. Importantly, the role of Foxp3 + Treg and Tr1 cells is not redundant once they are simultaneously expanded/induced in the same host. Moreover, our data show that long‐term tolerance induced by Foxp3 + Treg‐cell transfer is sustained by splenic Tr1 cells and functionally moves from the allograft to the spleen. Abstract : In a model of allogeneic pancreatic islet transplantation, Foxp3+ Treg cells exert their regulatory function within the allograft and initiate engraftment locally and in a non‐antigen‐specific manner, whereas CD4+CD25‐ T cells, which contain IL‐10‐producing Tr1 cells, act from the spleen and are key to the maintenance of long‐term tolerance. See editorial by Gill on page 1945.